La viande de dromadaire : production, aspects qualitatifs et aptitudes à la transformation - Kamoun M. (Elevage et alimentation du dromadaire, 1995)
This paper includes part of the work conducted for several years at l'Ecole Supérieure d'Agriculture de Mateur (Tunisia) on growth, fattening and carcass and meat quality in dromedaries. In order to find the best ration for growth, 16 young dromedaries, distributed in several groups, were fed a medium quality forage (wheat straw or oats hay of late harvest) ad libitum and concentrates in different quantities (0.4-3.2 kg) and of different qualities (15.8, 22.0 and 28.1 percent MAT per kg DM). Their intake during the tethered period ranged from 1.4 to 1.8 kg of DM per 100 kg of live weight. An amazing growth rate (280 g per day) has been observed using a medium quality ration. The growth of the youngest dromedaries has been modelled. The slaughtering males, aged 37+-12 (15-51) and weighing 477+-78 kg (301-560) provides 269+-46 kg (184-343) of carcass. The 5th quarter, blood and digestive tract content represent 21.72+-1.33 percent, 5.94+-3.6 percent and 15.82+-2.05 percent of the live weight respectively. Slaughtering yield, expressed as the carcass weight/empty live weight ratio, is 67.15+-3.6 percent (60.3-71.4 percent). This carcass contains, as an average, 57 percent meat, 25.5 percent bone and 16.9 percent fat. The tissues are unevenly distributed in the carcass. Meat, bone and fat composition is 59.3 percent, 4.5 percent and 36.2 percent for the fore half and 66.5, 14.9 and 17.3 percent for the hind half respectively. The hump, fat included, accounts for 8.6 percent of the carcass weight. Meat quality was studied in several muscles: Longissimus dorsi, Psoas major, Triceps Brachii caput longum, Semimembranosus, Semitendinosus and Vastus lateralis in 9 carcasses. A complete chemical analysis shows that dromedaries have a lean meat with high water content. 100 g of meat contain 22.3+-1.9 g of dry matter, being 18.7+-1.7 g protein, 1.0+-0.3 g ash and 2.6+-1.8 g fat. A sensorial analysis was conducted using mature meat, boiled in water for 40 minutes. It seems that age is not a predominant factor in yield variation and meat quality, in the case of dromedaries fed on the same diet and slaughtered between 15 and 51 months of age. Results concerning growth, quality and yield of carcass are discussed in order to draw some practical conclusions regarding, for instance, the best age for slaughtering.
Séminaire du Projet CEE-DGXII TS2*0233-C (EDB), 1992/10/09-10, Douz (Tunisia)